Analisis Determinan Permintaan Masyarakat Kota Padang Terhadap Jasa Pengiriman Paket Dikala Pandemi - Riri Enjeli; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This research is intended to interpret and explain the effect of income, price, timeliness of delivery, and quality of service on delivery requests at PT. Pos Indonesia (Persero) Padang during the pandemic. This research is a descriptive and inductive research, the data used are primary data and analyzed using Multiple Linear Regression. The estimation results show that revenue, price, on time delivery and service quality have a positive influence on the demand for package delivery at PT. Pos Padang during the pandemic.